Stem Cell Research and Therapy for Liver Disease - Navarro-Alvarez, Nalu; Soto-Gutierrez, Alejandro; Kobayashi, Naoya (Current Stem Cell Research & Therapy, 2009)
Liver failure is a catastrophic illness associated with the death of many patients who are waiting for transplantation. Currently there are no effective treatments for this disease, therefore scientists have paid their attention to the field of stem cells, which has helped to understand the pathogenesis of liver disease, expanded the drug discovery processes, and could potentially be used as an alternative therapy. Recent reports demonstrating the production of liver like cells derived from bone marrow and embryonic stem cells, have established a better understanding of the soluble factors and biochemical compounds that are essential in liver development. Although considerable progress has been made in differentiating stem cells into liver cells, current protocols have not yet produced cells with the phenotype of a complete mature hepatocyte. Therefore, the proper criteria for defining what constitutes a functional human stem cell-derived hepatocyte are required. This review describes the current challenges and future opportunities in Embryonic Stem cell differentiation to liver cells, and the appropriate characteristics needed for their future clinical use in the treatment of liver disease.
Keywords: Stem cell-derived hepatocytes